Mercury, arsenic, cadmium and lead in two commercial shark species (Sphyrna lewini and Caraharinus porosus) in Trinidad and Tobago. Issue 2 (30th June 2017) - Mohammed, Azad; Mohammed, Terry
Abstract: Sharks are long-lived apex predators which can accumulate toxic metals such as mercury and arsenic. Samples of Sphyrna lewini and Carcharinus porosus were collected from two commercial fish landing sites in Trinidad. Heavy metal concentrations were determined in the muscle, dorsal fin, vertebrae and liver using atomic absorption spectrometric. The provisional tolerable weekly intake (PTWI) and target hazard quotient (THQ) were determined to assess the potential health risks to consumers. Mercury levels ranged between 74–1899 μg/kg in S. lewini and 67–3268 μg/kg in C. porosus. Arsenic levels ranged between 144–2309 μg/kg in S. lewini and 762–6155 μg/kg in C. porosus. Cadmium levels generally ranged between 0.27–27.29 mg/kg in S. lewini and 0.6–29.89 mg/kg in C. porosus. Lead levels generally ranged between 0.14 and 208.81 mg/kg in S. lewini while C. porosus levels ranged between 0.30 and 459.94 mg/kg. The PTWI and THQ values suggest that consumption of these shark species can therefore be a major source of exposure to lead, cadmium, arsenic and mercury in humans and is likely to have potential health risk over long term exposure. Highlights: Sphyrna lewini and Carcharinus porosus are two of the most commonly consumed shark species in Trinidad and Tobago Metals in S. lewini ranged between 74-1899 µg/kg (Hg), 144-2309 µg/kg (As), 0.27-27.29 mg/kg (Cd) and 0.14-208.81 mg/kg (Pb) Metals in C. porosus ranged between 67-3268 µg/kg (Hg), 762-6155 µg/kg (As), 0.6-29.89 mg/kg (Cd), 0.30-459.94 mg/kg (Pb)